PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH KOMPETENSI PROFESIONAL DAN DISIPLIN KERJA TERHADAP KINERJA GURU (Studi Kasus Pada SMA Negeri di Kecamatan Pati Kabupaten Pati) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research is intended to examine the influence of professional competence and discipline performance to teachers’ work performance with the moderation of organizational culture. The specific purpose of this research is to examine the role of organizational culture moderates the influence of professional competence and discipline performance  to the teachers’ work performance. The usage of this research is to explain and expand the previous researches about the role of organizational culture  moderates the influence of professional competence  and discipline performance  to the teachers’ work performance. This research used the population of 166 teachers of state senior high school in Pati District, Pati Regency. The analysis technique used in this research is regression model moderate quasi. Based on the research result can be conducted that: professional competence  influences teachers’ work performance, discipline performance  influences the teachers’ work performance, organizational culture   strengthen  the influence of professional competence to teachers’ work performance, organizational culture  strengthen the influence of discipline performance  to the teachers’ work performance.Keywords: Professional Competence, Discipline Performance, Organizational Culturecand Teachers’ Work Performance